2017
DOI: 10.1038/jhh.2017.34
|View full text |Cite
|
Sign up to set email alerts
|

Familial hyperaldosteronism type III

Abstract: Primary aldosteronism is the most common form of endocrine hypertension. This disorder comprises both sporadic and familial forms. Four familial forms of primary aldosteronism (FH-I to FH-IV) have been described. FH-III is caused by germline mutations in KCNJ5, encoding the potassium channel Kir3.4 (also called GIRK4). These mutations alter the selectivity filter of the channel and lead to abnormal ion currents with loss of potassium selectivity, sodium influx and consequent increased intracellular calcium tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 35 publications
0
26
0
7
Order By: Relevance
“…It is widely accepted that this results in depolarization caused by the influx of Na + and a consequent influx of Ca 2+ through L-and T-type VGCCs followed by constitutive aldosterone secretion and hypertension (17,18). Since 2011, additional PA-linked mutations were discovered in KCNJ5 gene, in the pore region or in the cytosolic N-and C-terminal domains of GIRK4 (16,19,20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely accepted that this results in depolarization caused by the influx of Na + and a consequent influx of Ca 2+ through L-and T-type VGCCs followed by constitutive aldosterone secretion and hypertension (17,18). Since 2011, additional PA-linked mutations were discovered in KCNJ5 gene, in the pore region or in the cytosolic N-and C-terminal domains of GIRK4 (16,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Sporadic and familial mutations in KCNJ5 account for up to 70% of PA cases, often accompanied by adrenal adenoma (14,15). KCNJ5 germline mutations cause familial hyperaldosteronism type III, out of four types (16). In 2011, Choi et al (6) showed that PA-causing mutations in the GYG motif of the selectivity filter (G151R) or in close proximity to it (T158A and L168R) in GIRK4 cause a loss of selectivity for K + , yielding K + /Na + non-selective GIRK4 and GIRK1/4 channels (6).…”
Section: Introductionmentioning
confidence: 99%
“…KCNJ5 germline mutations associated with FH-III have been reported (Figure 2), for a total of 12 families and 22 affected family members (29). Notably, none of the further reported cases displayed the peculiar hormonal phenotype described by Geller et al (24).…”
mentioning
confidence: 99%
“…FH‐III was reported as a novel form of PA in 2008 and its molecular basis was uncovered in 2011, as a germline mutation of the KCNJ5 gene, encoding for the inward rectifying K + channel GIRK4. Twelve families and six germline mutations have been reported so far: most often affected patients display an extremely severe form of PA that requires bilateral adrenalectomy to control blood pressure . The Endocrine Society guideline recommends the genetic testing for FH‐III ( KCNJ5 target gene sequencing) in all patients with onset of PA at a very young age …”
Section: Primary Aldosteronismmentioning
confidence: 99%
“…Twelve families and six germline mutations have been reported so far: most often affected patients display an extremely severe form of PA that requires bilateral adrenalectomy to control blood pressure. 56 The Endocrine Society guideline recommends the genetic testing for…”
Section: Familial Primary Aldosteronismmentioning
confidence: 99%